2019
DOI: 10.3390/genes10060435
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Effects of FGF4 Retrogenes on Intervertebral Disc Disease in Dogs

Abstract: Two FGF4 retrogenes on chromosomes 12 (12-FGF4RG) and 18 (18-FGF4RG) contribute to short-limbed phenotypes in dogs. 12-FGF4RG has also been associated with intervertebral disc disease (IVDD). Both of these retrogenes were found to be widespread among dog breeds with allele frequencies ranging from 0.02 to 1; however, their additive contribution to disease is unknown. Surgical cases of IVDD (n = 569) were evaluated for age of onset, disc calcification, and genotypes for the FGF4 retrogenes. Multivariable linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
107
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(116 citation statements)
references
References 41 publications
7
107
0
1
Order By: Relevance
“…The chondrodystrophic degenerative phenotype is evident in the IVD as early as 10 weeks of age in dogs homozygous for the CFA12 FGF4 retrogene but is absent in breedmatched dogs lacking the mutation. These degenerative changes are similar to the detailed descriptions of degenerative "chondroid metamorphosis" in several chondrodystrophic dog breeds originally documented by Hansen 13 and those described in the Beagle and Dachshund breeds by Braund et al 5 Based on known genotyping data, 1,7 the dog breeds studied by Hansen 13 and Braund et al 5 (particularly Dachshunds and Beagles) would have had a high likelihood of carrying the CFA12 FGF4 retrogene due to the limited segregation of the allele within those breeds (allele frequencies of 0.99 and 1.0, respectively, based on UC Davis data). While Dachshunds also have a very high allele frequency for CFA18 FGF4 retrogene (0.99), Beagles do not appear to carry the CFA18 FGF4 retrogene.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The chondrodystrophic degenerative phenotype is evident in the IVD as early as 10 weeks of age in dogs homozygous for the CFA12 FGF4 retrogene but is absent in breedmatched dogs lacking the mutation. These degenerative changes are similar to the detailed descriptions of degenerative "chondroid metamorphosis" in several chondrodystrophic dog breeds originally documented by Hansen 13 and those described in the Beagle and Dachshund breeds by Braund et al 5 Based on known genotyping data, 1,7 the dog breeds studied by Hansen 13 and Braund et al 5 (particularly Dachshunds and Beagles) would have had a high likelihood of carrying the CFA12 FGF4 retrogene due to the limited segregation of the allele within those breeds (allele frequencies of 0.99 and 1.0, respectively, based on UC Davis data). While Dachshunds also have a very high allele frequency for CFA18 FGF4 retrogene (0.99), Beagles do not appear to carry the CFA18 FGF4 retrogene.…”
Section: Discussionsupporting
confidence: 82%
“…20,25,31 Classification based on gross morphological traits is problematic since a short-limbed phenotype may be associated with the CFA18 FGF4 retrogene or the CFA12 FGF4 retrogene, and only the latter appears to also result in the chondrodystrophic phenotype with concurrent degeneration of the IVD. 1,7 The presence of the CFA12 and CFA18 retrogenes is variable among many small dog breeds, and many breeds segregate both CFA12 and CFA18 FGF4 retrogenes. 1,7 Also, a single copy of the CFA12 FGF4 retrogene appears to be sufficient to cause IVD degeneration, but effects on limb length appear to be related to gene dose, making "longer legged" heterozygous animals more challenging to define as chondrodystrophic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Rhodesian Ridgebacks are owned by a lower proportion of the general population than Rottweilers (1.7% Rhodesian Ridgeback versus 7.9% Rottweiler ownership within VetCompass), which could have led to case-only studies underestimating the prevalence of osteosarcoma within Rhodesian Ridgebacks, because they present less often to the clinic owing to reduced ownership [5]. Having used a case and a control population, the current study design enabled us to minimize the likelihood of selective sampling, therefore we demonstrated that, as a proportion of Rhodesian Ridgebacks owned, their osteosarcoma risk is actually high [33,35]. Our results also differ from previous studies which determined that Staffordshire Bull Terriers (SBT) commonly present to veterinary clinics with osteosarcoma, and therefore cited SBT as an at-risk breed [5].…”
Section: Breed Variablementioning
confidence: 96%